2018
DOI: 10.3390/w10101468
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rainfall Temporal Distribution Models with Annual Maximum Rainfall Events in Seoul, Korea

Abstract: This study evaluated five models of rainfall temporal distribution (i.e., the Yen and Chow model, Mononobe model, alternating block method, Huff model, and Keifer and Chu model), with the annual maximum rainfall events selected from Seoul, Korea, from 1961 to 2016. Three different evaluation measures were considered: the absolute difference between the rainfall peaks of the model and the observed, the root mean square error, and the pattern correlation coefficient. Also, sensitivity analysis was conducted to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 18 publications
(5 reference statements)
2
19
0
Order By: Relevance
“…Furthermore, it could be expected that peak values continue to gradually decrease with the storm duration. These results are consistent with previous studies that similarly found that Huff's curves may underestimate peak runoff because they tend to over-smooth the representative mass curve [22,28,29]. On the other hand, there are also studies that have shown that Huff's curves can produce a wide range of corresponding flooding results (including above-average values) when combining different durations, quartiles, and isopleths [16].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Furthermore, it could be expected that peak values continue to gradually decrease with the storm duration. These results are consistent with previous studies that similarly found that Huff's curves may underestimate peak runoff because they tend to over-smooth the representative mass curve [22,28,29]. On the other hand, there are also studies that have shown that Huff's curves can produce a wide range of corresponding flooding results (including above-average values) when combining different durations, quartiles, and isopleths [16].…”
Section: Discussionsupporting
confidence: 91%
“…Although some authors have criticized frequency based methods, primarily because they do not represent actual historical rainfall [15,28], other authors have found that these methods agree well with historical storms. For example, Balbastre-Soldevila et al [22] found that the ABM method produced average peak flow rates in an urban catchment in Spain similar to several other geometrical methods and the AVM design storm, and Na and Yoo [29] reported that the ABM method was most similar to historical storms in Korea.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations